IDA PEDANDA KANIA: THE DOMINATION OF WOMEN IN HINDU RELIGIOUS RITUALS IN BALI - Keniten, Ida Ayu Putu Citta Mandala; Suardiana, I Wayan; Sutrisno, Nanang (E-Journal of Cultural Studies; Vol 18 No 1 (2025): Volume 18 Number 1 February 2025, 2025)
The dominance of power does not solely belong to men.  The Balinese Hindu community is familiar with the participation of women in various fields of life, especially in matters of religious rituals.  Through religion and its rituals, the Hindu community in Bali places women on par with men.  In the religious realm, women have roles and duties that are equally important as those of men.  The religious realm becomes one of the fields to observe the dominance of women.  This is represented through the presence of female religious leaders who hold the title of Ida Pedanda Kania.  Ida Pedanda Kania is a title bestowed upon women from Brahmana lineage who must first undergo all the purification rituals before they can serve as leaders of religious ceremonies.  Direct observation is the appropriate method to obtain in-depth data related to this phenomenon.  Using the social practice theory approach by Bourdieu was chosen to analyze the objectives of this research, which is to elaborate on the concepts of habitus, field, capital, and practice that will later answer how dominance in this religious field can be held by women with the title Ida Pedanda Kania.  In addition, the aim of this research is also to explain how social reality can be shaped by women who perform tasks in the public domain.  Using in-depth interview methods and conducting literature studies in data excavation is considered the most appropriate in this research.  This research was conducted in Karangasem Regency because, according to data, the highest number of Hindu religious leaders is located in Karangasem Regency.  Keyword:  the role of women, religious ceremonies, ceremonial leaders, performance, identity